AI for cars - Aulinas, Josep; Sjafrie, Hanky ([Place of publication not identified] : Chapman and Hall/CRC, 2021)
Artificial Intelligence (AI) is undoubtedly playing an increasingly significant role in automobile technology. In fact, cars inhabit one of just a few domains where you will find many AI innovations packed into a single product. AI for Cars provides a brief guided tour through many different AI landscapes including robotics, image and speech processing, recommender systems and onto deep learning, all within the automobile world. From pedestrian detection to driver monitoring to recommendation engines, the book discusses the background, research and progress thousands of talented engineers and researchers have achieved thus far, and their plans to deploy this life-saving technology all over the world.
ForewordPrefaceAI for Advanced Driver Assistance SystemsAutomatic ParkingTraffic Sign RecognitionDriver Monitoring System SummaryAI for Autonomous DrivingPerceptionPlanningMotion ControlSummaryAI for In-Vehicle Infotainment SystemsGesture ControlVoice AssistantUser Action PredictionSummaryAI for Research & DevelopmentAutomated Rules GenerationVirtual Testing Platform Synthetic Scenario GenerationSummaryAI for ServicesPredictive DiagnosticsPredictive MaintenanceDriver Behavior AnalysisSummaryThe Future of AI in CarsA Tale Of Two ParadigmsAI & Car SafetyAI & Car SecuritySummaryFurther ReadingReferences
OCLC-licensed vendor bibliographic record.
Keywords: COMPUTERS / Artificial Intelligence; COMPUTERS / Computer Graphics / Game Programming & Design; COMPUTERS / Computer Science; Automobiles -- Electronic equipment; Automobiles -- Automatic control; Artificial intelligence